Advocacy of Ukraine under constitutional reform - Бакаянова, Нана Мезенівна; Бакаянова, Н. М.; Бакаянова, Нана Мезеновна; Bakaianova, Nana M.; Свида, Олексій Георгійович; Свида, О. Г.; Свида, Алексей Георгиевич; Svyda, Oleksii H.; Деменчук, Марина Олександрівна; Деменчук, М. О.; Деменчук, Марина Александровна; Demenchuk, Maryna O.; et al. (Editorial Primmate S. A. S., 2019)
The relevance of the article is to find the answer to the question of the reasonableness of the abolition of the attorney 's monopoly in Ukraine. The object of the study of this article was the social legal relationship that arises when a person is represented in court by a lawyer. Both general scientific and legal research methods were used in the writing of the research. The article analyzed the draft laws on the abolition of the attorney's monopoly, the views of supranational bodies on this issue. The authors concluded that a lawyer should remain the exclusive, sole, "external" representative who provides professional legal assistance.

Актуальність статті полягає у пошуку відповіді на питання доцільності скасування адвокатської монополії в Україні. Об’єктом дослідження даної статті стали суспільні правовідносини, які виникають при представництві особи у суді. При написанні дослідження були використані як загальнонаукові так і спеціально-юридичні методи дослідження. В статті було проаналізовано проекти законів щодо скасування адвокатської монополії, висновки наднаціональних органів з даного питання. Авторами був зроблений висновок про те, що адвокат має залишатися виключним, єдиним, «зовнішнім» представником, який надає професійну правничу допомогу.
Bakaianova N. Advocacy of Ukraine under constitutional reform / N. Bakaianova, O. Svyda, M. Demenchuk, O. Dzhaburiya, O. Fomina // Amazonia Investiga. – Vol. 8. - Issue 22. – Editorial Primmate S. A. S., 2019. – P. 574-579.
Keywords: attorney; lawyer; bar; monopoly; адвокат; юрист; адвокатура; монополія; Research Subject Categories::LAW/JURISPRUDENCE